Feelings of health professionals facing user-mediated violence in the psychiatric hospital (Research, Society and Development, 2020)
Health workers are among the hardest hit by workplace violence. The rates of violence perpetrated by patients towards health professionals are known to be higher in psychiatry than in other fields. Objective: to investigate the understanding of healthcare professionals regarding the violence suffered in the psychiatric hospital; to describe the feelings experienced by these professionals; to discuss strategies proposed by professionals to minimize the effects of this violence; and to analyze the impact of the feeling / suffering of the professionals through the perspective of the worker's health. Quanti-qualitative study, carried out with health professionals from a public, federal psychiatric university hospital in the city of Rio de Janeiro. The violence caused by psychiatric patients causes physical and emotional damage to the professional, even though they consider it common, expected and believe they are prepared to deal with it. Stress was identified as the major consequence of experiencing workplace violence, followed by anger. The study suggests that the professionals daily prepare themselves through the understanding of the patient's clinical aspect, through empathy, through the bond built and through the involvement with the care given towards these individuals.